Health professionals' provision of lifestyle advice in the oncology context in the United Kingdom. (2nd March 2015) - Williams, K.; Beeken, R.J.; Fisher, A.; Wardle, J.
<x xml:space="preserve">Abstract</x> A healthy lifestyle following a cancer diagnosis is linked with better long‐term outcomes. Health professionals can play an important role in promoting healthy lifestyles after cancer, but little is known about the factors that influence whether or not they give lifestyle advice. We conducted an online survey to examine levels of, and predictors of, health professionals' provision of lifestyle advice to cancer patients in the United Kingdom. The survey included questions on awareness of lifestyle guidelines for cancer survivors, current practices with regard to giving advice on smoking, diet, exercise, weight and alcohol, and perceived barriers to giving advice. Nurses, surgeons and physicians (N = 460) responded to the survey. Many (36%) were not aware of any lifestyle guidelines for cancer survivors, but 87% reported giving some lifestyle advice; although this was lower for individual behaviours and often to <50% of patients. Respondents who were aware of lifestyle guidelines were more likely to give lifestyle advice on all behaviours (all OR's > 1.76, all P's < 0.05). Not believing lifestyle would affect outcomes was associated with lower odds of giving lifestyle advice (all OR's < 0.48, all P's < 0.05). Improved survivorship education for health professionals may increase the number of patients receiving lifestyle advice, and improve their long‐term outcomes.